A New Dynamic Scheme via Fractional Operators on Time Scale - Rashid, Saima; Aslam Noor, Muhammad; Nisar, Kottakkaran Sooppy; Baleanu, Dumitru; Rahman, Gauhar (Frontiers in Physics, 2020)
The present work investigates the applicability and effectiveness of the generalized Riemann-Liouville fractional integral operator integral method to obtain new Minkowski, Grüss type and several other associated dynamic variants on an arbitrary time scale, which are communicated as a combination of delta and fractional integrals. These inequalities extend some dynamic variants on time scales, and tie together and expand some integral inequalities. The present method is efficient, reliable, and it can be used as an alternative to establishing new solutions for different types of fractional differential equations applied in mathematical physics.